2006
DOI: 10.1002/ar.a.20397
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid‐induced fetal malformations are reduced by maternal immune stimulation with granulocyte‐macrophage colony‐stimulating factor or interferon‐γ

Abstract: Valproic acid, a drug commonly used to treat seizures and other psychiatric disorders, causes neural tube defects (NTDs) in exposed fetuses at a rate 20 times higher than in the general population. Failure of the neural tube to close during development results in exencephaly or anencephaly, as well as spina bifida. In mice, nonspecific activation of the maternal immune system can reduce fetal abnormalities caused by diverse etiologies, including diabetes-induced NTDs. We hypothesized that nonspecific activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…Spinal dysraphism includes dorsal midline defects derived from the secondary mal-development of ectoderm, mesoderm, and neurectoderm layers of tissue, and encompasses a variety of malformations including spina bifida, meningocele, meningomyelocele, syringomyelia, split cord anomalies (diplomyelia, diastematomyelia), and others (De Lahunta and Glass 2009). Environmental, genetic, and nutritional factors have been reported to cause neural tube defects in laboratory mice including drugs, physical agents (hyperthermia), vitamin excess or deficiency (folic acid), maternal infectious and metabolic diseases (Gutierrez et al 2006, Hrubec et al 2006. Among the metabolic diseases, Clinical signs in this case were consistent with a lumbosacral (L3-Cd4) spinal cord lesion.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Spinal dysraphism includes dorsal midline defects derived from the secondary mal-development of ectoderm, mesoderm, and neurectoderm layers of tissue, and encompasses a variety of malformations including spina bifida, meningocele, meningomyelocele, syringomyelia, split cord anomalies (diplomyelia, diastematomyelia), and others (De Lahunta and Glass 2009). Environmental, genetic, and nutritional factors have been reported to cause neural tube defects in laboratory mice including drugs, physical agents (hyperthermia), vitamin excess or deficiency (folic acid), maternal infectious and metabolic diseases (Gutierrez et al 2006, Hrubec et al 2006. Among the metabolic diseases, Clinical signs in this case were consistent with a lumbosacral (L3-Cd4) spinal cord lesion.…”
Section: Resultsmentioning
confidence: 64%
“…This congenital defect results from the failure of the neural tube closure with imperfect fusion of midline mesenchymal, neuroecotermal and cutaneous ectodermal components (Hoskins 2001). Failure of neural tube closure may arise from faulty induction of the underlying notochord or from other genetic, teratogenic, metabolic and nutritional factors (Hrubec et al 2006, McGeady et al 2006. Lesions observed with spinal dysraphism include spina bifida (defective fusion of the vertebral arch), hemivertebrae, fused vertebrae, vertebral canal stenosis, meningocele (protrusion of meninges through the defect), myelocele (protrusion of spinal cord through the defect) and meningomyelocele (protrusion of both meninges and spinal cord) (McGeady et al 2006, De Lahunta andGlass 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The fifth group was a non-immunestimulated non-diabetic control. We have demonstrated previously that administration of FCA, IFNγ or GM-CSF alone does not adversely alter fetal development, including development of the palate (Sharova et al, 2002; Prater et al, 2004; Hrubec et al, 2006a). Following an established procedure in our laboratory, immune stimulants were administered twice, first at 1 week and again at 1 day before STZ administration (Punareewattana et al, 2003; Punareewattana and Holladay, 2004).…”
Section: Methodsmentioning
confidence: 97%
“…Maternal immune stimulation reduced or blocked digit and limb defects (Prater et al, 2004), tail malformations and cleft palates (Sharova et al, 2002), and neural tube defects (Torchinsky et al, 1997; Punareewattana and Holladay, 2004; Hrubec et al, 2006a). Diverse means of stimulating the maternal immune system, such as intraperitoneal (IP) injection of inert particles, intrauterine injection of xenogenic lymphocytes or intrauterine or IP injection of immunostimulatory cytokines, have been effective in preventing or reducing fetal defects (Hrubec et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Non-specific maternal immune stimulation is protective in mice against birth malformations by chemical teratogens (Nomura et al 1990;Holladay et al 2000;Sharova et al 2000;Sharova et al 2002;Prater et al 2004;Hrubec et al 2006a). Studies by Hrubec et al (2006b) indicate a reduction of NTD (neural tube defects) and ocular defects induced by valproic acid in CD1 mice when dams were treated either with interferon g (IFNg) or granulocytemacrophage colony stimulating factor (GM-CSF). Prater et al (2004) similarly found a reduction of distal limb defects in offspring of IFNg-treated ICR (Institute of Cancer Research) mice exposed to methylnitrosourea (MNU).…”
Section: Introductionmentioning
confidence: 99%